2015
DOI: 10.3109/0886022x.2015.1062340
|View full text |Cite
|
Sign up to set email alerts
|

Renal cortical necrosis is a disappearing entity in obstetric acute kidney injury in developing countries: our three decade of experience from India

Abstract: Rational: Obstetrical complications are the commonest causes of Renal Cortical Necrosis (RCN). However, the overall incidence of RCN in obstetric acute kidney injury in developing countries has been decreasing in recent years. Objective: The aim of this study was to evaluate the changing profile of RCN in obstetric AKI over the last three decades. Methods: This single center study included patients with biopsy proven renal cortical necrosis over a period of 32 years from 1982 to 2014. The diagnosis of RCN was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…29 In a study by Prakash et al incidence of CN was found to be decreasing from 17% in 1982-1991 to 1.4% in 2003-2014. 30 The high incidence of CN in our study is probably due to referral of nonrecovering PRAKI to our center. In our study CN was due to puerperal sepsis (52%), PPH (22.9%), abruptio (20.83%), and TMA (4.1%).…”
Section: Discussionmentioning
confidence: 63%
“…29 In a study by Prakash et al incidence of CN was found to be decreasing from 17% in 1982-1991 to 1.4% in 2003-2014. 30 The high incidence of CN in our study is probably due to referral of nonrecovering PRAKI to our center. In our study CN was due to puerperal sepsis (52%), PPH (22.9%), abruptio (20.83%), and TMA (4.1%).…”
Section: Discussionmentioning
confidence: 63%
“…Thought to be as a result of severe renal ischemia secondary to hemorrhage or microvascular thrombosis, RCN is encountered in the developing world as a complication of pregnancy 1 . The exact pathogenesis of RCN in the obstetric setting has remained unsolved 2, 3, 4. Hemolysis and microangiopathy have been reported, but were ascribed to disseminated intravascular coagulation, perhaps secondary to sepsis or amniotic fluid embolism.…”
mentioning
confidence: 99%
“…Mortality rates at a single centre in the eastern India have shown a striking decline from 72% (1984-1994) to 19% (1995-2005) in the next decade [1]. In a study conducted by Prakash J, Pant J et al, the incidence of AKI has declined low enough to label it as a disappearing entity [15]. We have however encountered 17 autopsy cases of obstetric RCN of 13896 autopsies performed over a 12 year period at a tertiary care centre at a metropolis.…”
Section: Discussionmentioning
confidence: 99%